Subsurface Layer Investigation Using The Vertical Electrical Sounding (VES) in Muara Batu and Dewantara Sub-districts - Syafrizal; Nanda Novita; Muliani; Ikhwan Ananda Husna (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Research has been carried out that aims to determine the structure of the subsurface layers in the Muara Batu and Dewantara sub-districts using the Schlumberger array Vertical Electrical Sounding method. This research was conducted at 3 location points with a track length at each point of 600 m. The data in this study were measured using the SuperSting R8/IP resistivity meter and processed using the Ip2win software. The results obtained show that the subsurface layer at point VES1 consists of alluvium with a very low resistivity value (1.2 – 5.1 Ωm), VES2 consists of top soil, clays, gravels, tuffaceous, limestones, sandstones, and calcareous mudstones with a resistivity value of 4.8 – 39.0 Ωm, and VES3 consists of clays, gravels, silty clay, sandy silty clays, tuffaceous, silt, sand, calcareous mudstones and hard rocks with a resistivity value of 8.0 – 18.7 Ωm. The subsurface of VES1 is a layer that is saturated with water and is not dense so it has liquefaction potential. While VES2 and VES3 are dense layers so that buildings built in this area will be safer against earthquakes.